Filter selection for indoor-recirculating fan-coil unit respect to indoor-to-outdoor particle relationships and occupancy influences - Xu, Xiaoqian (2016)
This study investigated to what extent the indoor environment with air-recirculating fan-coil units (FCU) could protect human from outdoor particles during hazy days. Different grade filters (25%, 65%, 85%, and 95%) were attached onto FCU in various rooms in order to get a result of best-performed filter. Every day of monitoring was divided into two periods, which are static period from 12AM to 7AM and active period, which is from 8:30AM to 6:30PM. Performances of filters were examined respect to the indoor-to-outdoor particles relationships, as well as the occupancy influences. We put our focus onto the particles within 2.5µm in diameter, since this phase of particles could penetrate human lungs to cause severe health problems. Data was collected through Optical Particle Counter (OPC) and Optical Particle Sizer (OPS) from 09/09/2015 to 25/09/2015. Particles were separated into 6 size channels (0.3-0.5µm, 0.5-1.0 µm, 1.0-2.5 µm, 2.5-5.0 µm, 5.0-10.0 µm, >10.0 µm), the first 3 channels represented PM2.5 value. Then PM2.5 data from NEA official website was recorded. Real-time particle volume concentrations (PVC) for first 3 channels were plotted against 24 hours on day 23/09/2015, which is a typically unhealthy level hazy day. ANOVA test was conducted for indoor-to-outdoor ratio (I/O ratio) of every two filters with successive removal efficiency grades so as to figure out if there is difference in its mean value. Overall efficiency was also calculated based on various parameters to quantify real removal efficiency. Occupancy level was recorded on hourly basis, indoor-to-outdoor (I/O) ratio for both of static period and active period were compared by paired sample t-test to check whether the mean values for accumulated PM2.5 (bin1 to bin3) differs by the occupancy. Hence, a filter application effect was also be quantified. Indoor particles movement could be affected by various parameters, such as airflow rate and air-recirculation rate of FCU, air exchange rate (AER) of the room as well as infiltration factor. The results showed that the FCU with filter of 85% and 95% removal efficiency giving out similar and overall best performance among all, which can effectively reduce particle concentrations in indoor environment to a healthy level (37.5µg/m3).